The Cutting Season : A Novel - Locke, Attica (New York : Harper Perennial, 2013)
When the dead body of a young woman is found on the grounds of Belle Vie, the estate's manager, Caren Gray, launches her own investigation into Belle Vie's history, which leads her to a centuries old mystery involving the plantation's slave quarters--and her own past.
Keywords: Plantations -- Fiction; Murder -- Fiction -- Investigation; Louisiana -- Fiction; Mystery fiction; Suspense fiction